Comparative study on five kinds of cytokines in the tissues of Chinese giant salamander (Andrias davidianus) of different developmental stages. Issue 1 (November 2021) - Qian, J; Zhai, X Y; Guo, L; Chen, W G; Fu, J J; Shi, M Y
Abstract: By using of the double antibody sandwich method of ELISA, the activities of five cytokines including IL-2, IL-4, IFN-α, IFN-β and TNF-α from the blood serum, liver, intestine and spleen at two developmental stages of Chinese giant salamander ( Andrias davidianus ) were determined to analyze the distribution of the cytokines. The result indicated that five cytokines were found in these four tissues, while their activities were different in different tissues and different ages. The highest activity of IL-2 and IL-4 was all present in blood serum of two different ages. The activity of IFN-α was the highest in blood serum of 1-year-old and in spleen of 2-year-old, respectively. The activity of IFN-β was also highest in blood serum of two different ages. The activity of TNF-α was highest in liver of two different ages. Thus, this study provides convincing reference for blood serum and liver as the most important distribution area of Chinese giant salamander.